2006
DOI: 10.1007/s11255-005-1661-7
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Endurance Cycle Ride Associated with a Significant Rise in PSA

Abstract: A number of disease processes are associated with an elevation in serum PSA. However, several studies have concluded that cycling is not an activity associated with an elevation in PSA. Herein, we summarise the literature and describe the case of a 54-year-old man who had presented to his General Practitioner (GP) with lower urinary tract symptoms 3 days after the completion of a 39-h endurance cycle ride. The PSA level was initially found to be elevated at 28 ng/ml, but decreased to 4 ng/ml and then 2 ng/ml w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 5 publications
2
8
1
1
Order By: Relevance
“…Long-distance biking is an excellent model to study the combined effects of mechanical prostate stimulation by bicycle riding and strenuous endurance exercise [ 2 ]. Mejak and coworkers demonstrated that cycling causes a significant increase in total PSA level when measured within 5 min post-cycling [ 3 ], whereas similar results were also achieved in other studies [ 4 , 5 , 6 , 7 ]. On the other hand, other researchers report no changes in PSA level following cycling [ 8 , 9 , 10 ], showing the controversy of these types of studies.…”
Section: Introductionsupporting
confidence: 70%
“…Long-distance biking is an excellent model to study the combined effects of mechanical prostate stimulation by bicycle riding and strenuous endurance exercise [ 2 ]. Mejak and coworkers demonstrated that cycling causes a significant increase in total PSA level when measured within 5 min post-cycling [ 3 ], whereas similar results were also achieved in other studies [ 4 , 5 , 6 , 7 ]. On the other hand, other researchers report no changes in PSA level following cycling [ 8 , 9 , 10 ], showing the controversy of these types of studies.…”
Section: Introductionsupporting
confidence: 70%
“…3244 ng/ml) das Radfahren komplett eingestellt hatten [6,24]. Die Autoren vermuten, dass die wiederholte mechanische Reizung der Prostata beim Fahrradfahren die Konzentration des PSA erhöht hat.…”
Section: Diskussionunclassified
“…A comprehensive analysis of the 12 previous research reports regarding PSA and cycling, the majority of studies have shown no change to PSA subsequent to cycling [16]–[22], however, three prospective studies [22]–[24] and 2 published case reports [25], [26] have shown an increase in PSA with cycling. The methodologies of these cycling studies varied in many ways from each other, including the age ranges tested, timing of the post-cycling PSA testing, sample size, and the duration and intensity of cycling, and therefore discourage effective comparison.…”
Section: Introductionmentioning
confidence: 99%